2017
DOI: 10.4269/ajtmh.16-0915
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia australis and Queensland Tick Typhus: A Rickettsial Spotted Fever Group Infection in Australia

Abstract: , the etiologic agent of Queensland tick typhus (QTT), is increasingly being recognized as a cause of community-acquired acute febrile illness in eastern Australia. Changing human population demographics, climate change, and increased understanding of expanding vector distribution indicate QTT is an emerging public health threat. This review summarizes the epidemiology, pathogenesis, clinical features, treatment principles, and future directions of this disease. Increased recognition of QTT will enable conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…3,22 One OTU completely matched the human pathogen, R. akari. 23 Some OTUs were also very similar to some human pathogens, including Rickettsia aeschilimannii, 24 Rickettsia felis, 25 and Rickettsia australis, 26 although the genetic diversity among the strains was low. Previous reports have shown that bacteria very similar to R. felis, R. australis, and R. akari were detected in L. scutellare mites in China and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…3,22 One OTU completely matched the human pathogen, R. akari. 23 Some OTUs were also very similar to some human pathogens, including Rickettsia aeschilimannii, 24 Rickettsia felis, 25 and Rickettsia australis, 26 although the genetic diversity among the strains was low. Previous reports have shown that bacteria very similar to R. felis, R. australis, and R. akari were detected in L. scutellare mites in China and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…TwKM02 ( Rickettsia australis cluster) in L. deliense collected from rodents in Kinmen and Matsu. While R. rhipicephali is an unlikely human pathogen [ 81 ], R. australis (TRG) is the etiologic agent of Queensland tick typhus [ 82 ], which occurs primarily in northeastern Australia [ 49 ]. Tsai et al [ 64 ] then isolated a novel SFG rickettsiae, Rickettsia sp.…”
Section: Emerging Vector-borne Rickettsiosesmentioning
confidence: 99%
“…Rickettsia australis is the agent responsible for the illness called Queensland tick typhus and transmitted by Ixodes holocyclus ticks along the eastern coast of Australia. 50 Disease attributed to Rickettsia felis has been termed flea-borne spotted fever. The organism was originally described within a laboratory colony of cat fleas (Ctenocephalides felis).…”
Section: Transitional Group Rickettsiosesmentioning
confidence: 99%
“…49 The clinical presentation of Queensland tick typhus is similar to aforementioned SFG rickettsioses with maculopapular rash in 90% and eschar in up to 65% with associated regional lymphadenopathy. 50 Although more often mild, severe and fatal cases have been documented. 66 Flea-borne spotted fever also appears to to have manifestations that are on the milder side of the clinical spectrum when compared to other SFG rickettsioses.…”
Section: Transitional Group Rickettsiosesmentioning
confidence: 99%